Repurposing Ivacaftor for treatment of staphylococcus aureus infections - Thakare, R.; Das, S.; Vasudevan, N.; Jachak, G.R.; Reddy, D.S.; Dasgupta, A.; Chopra, S. (International Journal of Antimicrobial Agents, 2017)
Drug repurposing of non-antimicrobials is a novel method to augment a seriously depleted drug pipeline for targeting drug–resistant pathogens. This article highlights the potent antimicrobial activity of Ivacaftor against Staphylococcus aureus, including vancomycin– and other multidrug–resistant strains. The potent activity of Ivacaftor in vivo is also demonstrated in a murine neutropenic thigh infection model. Taken together, these results support the potential of Ivacaftor as an antimicrobial agent for the treatment of staphylococcal infections. © 2017 Elsevier B.V. and International Society of Chemotherapy